Murine CXCR3+CXCR6+γδT Cells Reside in the Liver and Provide Protection Against HBV Infection - Wang, Yanan; Guan, Yun; Hu, Yuan; Li, Yan; Lu, Nan; Zhang, Cai (Frontiers in Immunology, 2022)
Gamma delta (γδ) T cells play a key role in the innate immune response and serve as the first line of defense against infection and tumors. These cells are defined as tissue-resident lymphocytes in skin, lung, and intestinal mucosa. They are also relatively abundant in the liver; however, little is known about the residency of hepatic γδT cells. By comparing the phenotype of murine γδT cells in liver, spleen, thymus, and small intestine, a CXCR3+CXCR6+ γδT-cell subset with tissue-resident characteristics was found in liver tissue from embryos through adults. Liver sinusoidal endothelial cells mediated retention of CXCR3+CXCR6+ γδT cells through the interactions between CXCR3 and CXCR6 and their chemokines. During acute HBV infection, CXCR3+CXCR6+ γδT cells produced high levels of IFN-γ and adoptive transfer of CXCR3+CXCR6+ γδT cells into acute HBV-infected TCRδ−/− mice leading to lower HBsAg and HBeAg expression. It is suggested that liver resident CXCR3+CXCR6+ γδT cells play a protective role during acute HBV infection. Strategies aimed at expanding and activating liver resident CXCR3+CXCR6+ γδT cells both in vivo or in vitro have great prospects for use in immunotherapy that specifically targets acute HBV infection.